Ésteres combustíveis em motor de ciclo diesel sob condições de pré-aquecimento e variação no avanço de injeção - Machado, Paulo Romeu Moreira (2008)
The renewed interest in energy for biomass is supported by the need for different energy sources and the need to protect the environment. Recently, because of increases in crude oil prices, limited resources of fossil oil and environmental concerns there has been renewed focus on vegetable oils and animal fats to make a biodiesel fuel. What is known as biodiesel (methyl or ethyl esters) is a vegetable oil or animal fat chemically treated to replace traditional diesel fuel. Performance parameters and exhaust emissions of a diesel engine fuelled with sunflower and beef tallow ethyl esters and a blend of ethyl and methyl esters, subjected to pre-heating at two temperatures ranges, namely T55 (50 to 60ºC) and T75 (70 to 80ºC), in order to lower its viscosities, have been investigated. Tests were carried out at full load conditions in a four cylinders, four-stroke indirect injection diesel engine. Engine tests, short-term, were conducted at a range speed from 1900 to 4400 rpm. The injection timing was retarded from the manufacturer s recommended setting. The tests were carried out using the same engine and test procedures so that comparative assessments may be made. The tests data were used for evaluating the brake power, exhaust gas temperatures, specific fuel consumption and gaseous emissions. The analysis of the results determined that the level of pre-heating have influence on the performance for used esters. The tests performed at T55 showed the best values of torque (N.m), power (kW) and specific fuel consumption (g.kW-1.h-1) that the tests performed at T75. The bests experiments results were obtained with sunflower ethyl ester and the blend containing 50,0% sunflower ethyl ester and 50,0% beef tallow methyl ester, at -2º BTDC and T55 temperature range. The findings showed that, by using biodiesel, harmful emissions (CO, HC and NOx) can be reduced to some extent of B2 by adjusting the injection pump timing properly and pre-heating of fuel.